Lower Limb Ischaemic Symptoms in the Young Patient: Popliteal Artery Entrapment. Issue 4 (1st December 2012) - Roy, S; Vohra, R; Duddy, M; Tiwari, A
Abstract : This case report describes a case of Popliteal Entrapment Syndrome causing unilateral ischaemic claudication symptoms in an otherwise healthy soldier. The condition is rare but is an important cause of exercise related leg pain; untreated it can progress to structural arterial damage requiring reconstruction. Early identification of such cases may allow less invasive treatment.